Cost-effectiveness of home care compared to hospital care in patients with chronic obstructive pulmonary disease (COPD): a systematic review - Vidigal, Maria Tereza Campos; Borges, Guilherme Henrique; Rabelo, Diogo Henrique; de Andrade Vieira, Walbert; Nascimento, Gustavo G.; Lima, Rafael Rodrigues; Costa, Márcio Magno; Herval, Álex Moreira; Paranhos, Luiz Renato (Frontiers in Medicine, 2024)
Background To compare, through a systematic literature review, the cost-effectiveness ratio of home care compared to hospital care for following up patients with chronic obstructive pulmonary disease (COPD). Methods This review was registered in PROSPERO, and the bibliographic search was performed in six primary databases [MedLine (via PubMed), Scopus, LILACS, SciELO, Web of Science, and Embase], two dedicated databases for economic studies (NHS Economic Evaluation Database (NHS EED) and Cost-Effectiveness Analysis (CEA) Registry), and two databases for partially searching the “gray literature” (DansEasy and ProQuest). This review only included studies that compared home and hospital care for patients diagnosed with COPD, regardless of publication year or language. Two reviewers selected the studies, extracted the data, and assessed the risk of bias independently. A JBI tool was used for risk of bias assessment. Results and discussion 7,279 studies were found, of which 14 met the eligibility criteria. Only one study adequately met all items of the risk of bias assessment. Thirteen studies found lower costs and higher effectiveness for home care. Home care showed a better cost-effectiveness ratio than hospital care for COPD patients. Regarding effectiveness, there is no possibility of choosing a more effective care for COPD patients, given the incipience of the data presented on eligible studies. However, considering the analyzed data refer only to high-income countries, caution is required when extrapolating this conclusion to low- and low-middle-income countries. Systematic review registration https://www.crd.york.ac.uk/prospero/, identifier CRD42022319488.